Efficient Perovskite Solar Cells with a Novel Aggregation‐Induced Emission Molecule as Hole‐Transport Material. Issue 2 (23rd July 2019) - Cao, Yulin; Chen, Wei; Sun, Huiliang; Wang, Dong; Chen, Peng; Djurišić, Aleksandra B.; Zhu, Yudong; Tu, Bao; Guo, Xugang; Tang, Ben-Zhong; He, Zhubing
Abstract : Organic hole‐transport materials (HTMs) are very promising for perovskite solar cells (PSCs) because the molecule structure is engineered via facile chemical routes. Herein, an aggregation‐induced emission (AIE) molecule, 2‐(2, 7‐bis(4‐(bis(4‐methoxyphenyl)amino)phenyl)‐9 H ‐fluoren‐9‐ylidene)malononitrile (TFM), is successfully employed for the first time as a HTM in an inverted planar PSC, obtaining a promising device performance superior to that of the control device with poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) HTM. An optimal power conversion efficiency (PCE) of 16.03% is obtained for the TFM‐based PSCs with a J sc of 22.68 mA cm −2, V oc of 0.97 V and FF of 72.9%, while that of the control PEDOT:PSS‐based device is 14.95%. Steady‐state and time‐resolved photoluminescence results reveal suppressed nonradiative recombination at the TFM/perovskite interface that is attributed to the effective passivation of the uncoordinated Pb at the perovskite surface by the CN − groups of TFM molecules, as confirmed by X‐ray photoelectronic spectroscopy measurements. In addition to the passivation, the hydrophobic character of TFM films also contributes to the improved device stability. The findings demonstrate the potential of AIE molecules in PSCs and also paves a novel way to improve device performance and stability by molecular structure engineering of AIE molecules in the future. Abstract : An aggregation‐induced emission (AIE) molecule is successfully employed as an effective hole transport material in an inverted planar perovskite solar cell. The improvement of perovskite crystallinity and the suppression of nonradiative recombination at the AIE/perovskite interface result in enhanced device performance and stability as compared with the poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS)‐based control one.